2012
DOI: 10.1124/jpet.112.196980
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antifungal Activity of Derivatives of 2- and 3-Benzofurancarboxylic Acids

Abstract: We found that amiodarone has potent antifungal activity against a broad range of fungi, potentially defining a new class of antimycotics. Investigations into its molecular mechanisms showed amiodarone mobilized intracellular Ca 2ϩ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 52 publications
0
9
1
Order By: Relevance
“…One of such compounds (denominated 4 in this previous report) was able to completely arrest C. neoformans growth at a concentration of 20 µM, while it affected human leukemia K-562 cells only at concentrations higher than 30 µM. Interestingly, this drug was able to enhance the Ca 2+ mobilization produced by amiodarone in yeast (Hejchman et al, 2012).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…One of such compounds (denominated 4 in this previous report) was able to completely arrest C. neoformans growth at a concentration of 20 µM, while it affected human leukemia K-562 cells only at concentrations higher than 30 µM. Interestingly, this drug was able to enhance the Ca 2+ mobilization produced by amiodarone in yeast (Hejchman et al, 2012).…”
Section: Introductionmentioning
confidence: 88%
“…1. Chemical structure of (A) the benzofuran derivative (AMIODER), based on the structure of (B) amiodarone, used in this work (Hejchman et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen containing heterocycles possess many biological activities, such as anti-inflammatory [75], anticancer [76], antioxidative [77], antiviral [78] and antifungal activity [79]. It was a major challenge for organic chemists to synthesize heterocyclic compounds with a high degree of selectivity, specially the benzo[b]furan from a simple synthon.…”
Section: In 2009mentioning
confidence: 99%
“…Also, recent studies showed that novel 1,4,5,6,7,8-hexahydroquinoline derivatives have significant cytotoxic activity against different human cancer cell lines [10][11][12]. Also, literature survey documented that various benzofuran compounds are known to possess important biological properties, including antimicrobial [13][14][15], antifungal [16], antiviral [17], anti-inflammatory [18,19], antidiabetic [20], antioxidant [21,22]. Moreover, many benzofuran derivatives have shown remarkable anticancer activity [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%